2019
DOI: 10.3390/nu11051157
|View full text |Cite
|
Sign up to set email alerts
|

Role of Calcium and Low-Fat Dairy Foods in Weight-Loss Outcomes Revisited: Results from the Randomized Trial of Effects on Bone and Body Composition in Overweight/Obese Postmenopausal Women

Abstract: Several studies have investigated the possibility of dairy foods and calcium (Ca) mediating weight and body composition, but a consensus has not been reached. We aimed to investigate weight-loss-related outcomes during intervention with low-fat dairy foods or Ca + vitamin D supplements, both as complements to hypocaloric diets. Overweight/obese Caucasian, early-postmenopausal women (n = 135) were recruited for a 6 month energy-restricted weight loss study complemented with either low-fat dairy foods (D; 4–5 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(68 citation statements)
references
References 99 publications
2
63
2
1
Order By: Relevance
“…Calcium and magnesium are well known for their role in bone, muscle, and adipose tissue health [ 64 , 80 ], and they will not be discussed further here. However, an interesting recent study conducted in Croatian nursing homes reported a low dietary calcium intake (528 ± 279 mg/day women and 653 ± 296 mg/day, men) in 292 older (>80 years) participants [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium and magnesium are well known for their role in bone, muscle, and adipose tissue health [ 64 , 80 ], and they will not be discussed further here. However, an interesting recent study conducted in Croatian nursing homes reported a low dietary calcium intake (528 ± 279 mg/day women and 653 ± 296 mg/day, men) in 292 older (>80 years) participants [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium and magnesium are best known for their roles in bone metabolism and muscle health and the former, along with dairy products, is also implicated in weight loss/maintenance by attenuating adiposity [ 62 ]. Based on national surveys, calcium and magnesium are still at a lower or marginal intake in the US population, even when supplements are taken into consideration [ 44 ].…”
Section: Precision Nutrition For Osa and Lgci In Good Times And Inmentioning
confidence: 99%
“…Based on national surveys, calcium and magnesium are still at a lower or marginal intake in the US population, even when supplements are taken into consideration [ 44 ]. An abundance of literature is available for the beneficial effect of calcium on bone and weight [ 32 , 62 ] and the role of magnesium in muscle [ 63 ] and adipose tissue through its regulation of insulin sensitivity and serum glucose [ 64 , 65 ]. Therefore, these functions will not be elaborated on here.…”
Section: Precision Nutrition For Osa and Lgci In Good Times And Inmentioning
confidence: 99%
“…Epidemiological studies have shown that many people with obesity have inadequate intake of certain micronutrients, such as deficient in iron, calcium, magnesium, zinc and copper (Agarwal et al, 2015;Astrup & Bügel, 2019). Various studies suggested that there was a negative correlation between calcium intake and BMI, and that calcium intake can improve weight outcomes in overweight or obese individuals (Ilich et al, 2019;Lee & Cho, 2017;Rautiainen et al, 2016;Wadolowska et al, 2018;Zhu et al, 2013). A cross-sectional study in Poland showed that daily intake of minerals in postmenopausal females was related to BMI, overweight individuals have lower potassium and magnesium intakes, and higher sodium intake (Głąbska et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…High-dietary phosphorus, especially from foods processed with phosphate salts may be positively correlated with obesity (Anderson, 2013). Recent studies have shown that the mineral supplements can reduce body weight and inflammation and improve lipid metabolism, such as mineral supplements of calcium (Ilich et al, 2019), magnesium (De Baaij, Hoenderop & Bindels, 2015), zinc, copper and selenium (Khorsandi et al, 2019;Lee, 2018;Roman, Jitaru & Barbante, 2014).…”
Section: Introductionmentioning
confidence: 99%